2017
DOI: 10.5812/jjcdc.14427
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Resilience via Social Support and Illness Perceptions Among Patients Undergoing Hemodialysis

Abstract: Background and Objectives: Chronic renal disease is a threatening condition for the health, economic, and social status of the affected person and his/her family. Patients undergoing hemodialysis encounter mental and health problems; the current study aimed at predicting resilience via social support and illness perceptions among patients undergoing hemodialysis. Methods:The current descriptive-correlational study had a statistical population including 308 patients undergoing hemodialysis in Kerman, Iran, in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…Even if it cannot overcome stressful situations in some circumstances, it enables people to be more optimistic by reducing their anxiety and increasing their self-esteem. It might also help people cope with challenging situations and create new solutions, hence making them more satisfied with life (10,38).…”
Section: Discussionmentioning
confidence: 99%
“…Even if it cannot overcome stressful situations in some circumstances, it enables people to be more optimistic by reducing their anxiety and increasing their self-esteem. It might also help people cope with challenging situations and create new solutions, hence making them more satisfied with life (10,38).…”
Section: Discussionmentioning
confidence: 99%
“…The results have shown a strong negative correlation between resilience and mental distress in these people, so the lower the resilience score, the higher the possibility of mental distress in these people. According to the researchers, the resilience measurement tool has good validity and reliability for assessing different dimensions of resilience [7]. Nevertheless, there is still no tool available in Iran that has suitable psychometric properties to measure the resilience of MS patients for screening purposes and monitoring the impact of supportive interventions.…”
Section: Introductionmentioning
confidence: 99%
“… 16 In a study by Hajmohammadi and Shirazi in Iran, the resilience in HD patients was reported to be at a moderate level, which can be increased by self-care education. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%